Developing A Digital Psychoeducational Tool to Reduce Loneliness in Older Adults: A Design Case Study. Issue 6 (3rd April 2022) - Al Mahmud, Abdullah; Long, Katrina M.; Harrington, Karra D.; Casey, Kit; Bhar, Sunil; Curran, Simon; Hunter, Kristie; Lim, Michelle H.
ABSTRACT: This paper presents the co-design process of a digital tool that may prevent or alleviate feelings of loneliness in older adults. Six workshops were conducted with older adults ( n = 34) aged between 65–80 years old to investigate the role of technology in maintaining and establishing meaningful relationships. Participants' contributions throughout the workshops were used to inform the design and development of a web-based loneliness intervention for older adults called ElderConnect . ElderConnect is a web-based application that supports older adults to identify, prevent, and alleviate feelings of loneliness by providing knowledge and strategies to initiate new social connections and maintain existing connections. Several challenges were identified while co-designing the application with older adults, and suggestions are provided in this paper to overcome such challenges. The study highlights how to include older adults' concerns regarding technologies within an iterative co-design process, leading to an endorsed final product.